2007
DOI: 10.1074/jbc.m611007200
|View full text |Cite
|
Sign up to set email alerts
|

SSB Protein Limits RecOR Binding onto Single-stranded DNA

Abstract: The RecO and RecR proteins form a complex that promotes the nucleation of RecA protein filaments onto SSB proteincoated single-stranded DNA (ssDNA). However, even when RecO and RecR proteins are provided at optimal concentrations, the loading of RecA protein is surprisingly slow, typically proceeding with a lag of 10 min or more. The rate-limiting step in RecOR-promoted RecA nucleation is the binding of RecOR protein to ssDNA, which is inhibited by SSB protein despite the documented interaction between RecO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 79 publications
5
93
0
Order By: Relevance
“…interacts with the C-terminal tail of SSB (36,37). To further test the existence and importance of this interaction in the strand displacement reaction, we replaced wild-type SSB with two C-terminal SSB proteins that had 8 and 42 amino acids deleted from their C termini (30,31). We observed that neither supported strand displacement (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…interacts with the C-terminal tail of SSB (36,37). To further test the existence and importance of this interaction in the strand displacement reaction, we replaced wild-type SSB with two C-terminal SSB proteins that had 8 and 42 amino acids deleted from their C termini (30,31). We observed that neither supported strand displacement (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…RecA (d)ATP Hydrolysis Assays-The ssDNA-dependent dATP or ATP (denoted as (d)ATP) hydrolysis activity of RecA protein was performed as described (6,24). RecA-mediated (d)ATP hydrolysis was not affected within the first 180 min of incubation, even upon binding a silicon nanowire transistor (25).…”
Section: Methodsmentioning
confidence: 99%
“…As previously reported (24,26), the lag time, which represents the delay in reaction progress relative to a theoretically reaction curve lacking it, was derived from the time intercept of a linear regression line fit to the steady state portion of data in (d)ATP hydrolysis assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C-terminally deleted variants of SSB, in which the C-terminal domain (up to 42 residues) has been removed, bind somewhat more tightly to ssDNA than does wild type SSB (77,78). In trials to date, no ssDNA binding deficiency (relative to wild type SSB) has been detected with the SSB⌬C8 variant (76,79). Four of the final eight residues of E. coli SSB are aspartate residues, and many proteins interact with this acidic SSB C terminus, (73, 79 -91).…”
Section: Deleting 8 Amino Acid Residues From the Ssb C Terminus Decrementioning
confidence: 99%